2015
DOI: 10.1177/2158244015581189
|View full text |Cite
|
Sign up to set email alerts
|

Policing Transgender People

Abstract: Police policy documents often articulate strategies and approaches that police organizations want to implement in their efforts to break down barriers with minority groups. However, most police policy documents are written for police audiences and not for members of the public. Police policy documents serve as a reflection of the aspirations of the agency and not necessarily the practice of the officers. Differential policing has been a salient experience for members of transgender communities because, as indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…From an international research perspective, MilesJohnson (2013aMilesJohnson ( , 2013bMilesJohnson ( , 2015aMilesJohnson ( , 2015bMilesJohnson ( , 2015cMilesJohnson ( , 2016 has examined transgender identities within Australia. MilesJohnson 2015afound that the damaging effects of police hostility and discrimination toward the transgender community have stemmed from the aggression directed toward transgender identities in general.…”
Section: Previous Research On Non-police Transgender Perceptions Of Tmentioning
confidence: 99%
“…From an international research perspective, MilesJohnson (2013aMilesJohnson ( , 2013bMilesJohnson ( , 2015aMilesJohnson ( , 2015bMilesJohnson ( , 2015cMilesJohnson ( , 2016 has examined transgender identities within Australia. MilesJohnson 2015afound that the damaging effects of police hostility and discrimination toward the transgender community have stemmed from the aggression directed toward transgender identities in general.…”
Section: Previous Research On Non-police Transgender Perceptions Of Tmentioning
confidence: 99%
“…While some staff reported understanding the need for sensitivity on some topics, as well as taking consideration and care to not ‘put the spotlight’ on trans people and their needs, other staff reported that trans issues were not of concern, instead focusing on the general issues of the prison setting (Marlow et al., 2015 , p. 249). The latter attitude, within a transformative framework, is another act of violence toward trans people, which in turn actively contributes to diminishing and erasing the lives and experiences of trans people in carceral settings, in turn placing them at greater risk of harm (Lamble, 2014 , 2015 ; Miles-Johnson, 2015 ; Mitchell et al., 2022 ; Spade, 2015 ; Stanley & Smith, 2015 ; Stanley et al., 2012). Some studies positively highlighted the impact of reformist organizational approaches and attitudes (such as policies and procedures) had on attitudes and the treatment of incarcerated trans person (Walker, 2020 ; White Hughto et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach would provide an opportunity to reflect on and address the pervasive systemic discrimination and violence faced by trans adults and youth that hinders access to and excludes them from employment, housing, education, health, and family, and that aims to reduce the very need to undertake activities deemed illegal in order to survive (Stanley, 2015 ). To this end, eliminating transphobia through education rooted in social justice, and building cultures and institutions that embrace trans embodiment would not only contribute to reducing trans-biased policing practices (Grant et al., 2011 ; Miles-Johnson, 2015 ; Mitchell et al., 2022 ; Poteat et al., 2023 ) informing the over-representation of trans people in the prison system (Clark et al., 2023 ; Hughto et al., 2022 ; Reisner et al., 2014 ), but also make possible alternative methods of accountability for those who do harms (Lamble, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PWMI may perceive that they have a stigmatised position in society due to their historically marginalised ailment, PWMI may expect to receive disrespectful police treatment, and as such, may pay more attention to the kind of treatment they receive from the police (McCluskey 2003;Watson and Angell 2007). McCluskey (2003) initially identified that PWMI value procedural justice by conducting research with irrational persons (defined in the study as persons who are intoxicated, mentally ill, or strongly influenced by heightened emotions), and demonstrated that irrational persons were more likely than rational persons to comply with fair and respectful police directives and were more likely to rebel against disrespectful police treatment. Subsequent research specifically regarding PWMI corroborates that PWMI value procedural justice in police interactions Watson and Angell 2013;Watson et al 2008;Watson et al 2010).…”
Section: Introductionmentioning
confidence: 99%